Static and genetic phenomenology : the transcendental turn in Binswanger’s psychiatry - Sganga, Michela (Scenari, 2021)
The present contributions aims to investigate the importance of Edmund Husserl’s transcendental phenomenology in latest Binswanger’s works, especially considering his phenomenological studies about schizophrenia. Indeed, the interest in a deeper comprehension of schizophrenic experience leads Binswanger to integrate both static and genetic phenomenology into Daseinsanalytic method, in order to achieve a wider sight on schizophrenic psychoses and their development. Due to genetic phenomenology Husserl focuses on the two main conscience structures – intentionality and temporality – dealing with constitution of the experience as a whole. What emerges behind experience itself is the rich background of passive synthesis and the typical aproblematic feature of living the common world.